A different pond - Phi, Bao, 1975-; Bui, Thi (North Mankato, Minnesota : Capstone Young Readers, a Capstone imprint, 2017)
"As a young boy, Bao Phi awoke early, hours before his father's long workday began, to fish on the shores of a small pond in Minneapolis. Unlike many other anglers, Bao and his father fished for food, not recreation. Between hope-filled casts, Bao's father told him about a different pond in their homeland of Vietnam"-- Provided by publisher.
Keywords: Vietnamese Americans -- Juvenile fiction; Immigrants -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Fishing stories; Vietnamese Americans -- Fiction; Immigrants -- Fiction; Fathers and sons -- Fiction; Fishing -- Fiction; Picture books